KORELASI LAYANAN INFORMASI DIGITAL DENGAN KEMANDIRIAN PESERTA DIDIK JURUSAN ILMU PENGETAHUAN SOSIAL UNTUK MELANJUTKAN STUDI PADA PERGURUAN TINGGI - Septian Aji Permana (Universitas Muria Kudus, 2020)
This study aims to determine the correlation of digital information services with self-adjustment (independence of character) of students majoring in social studies in obtaining higher education information.This study uses a quantitative approach. The population of this study was all social studies students of class X. XI, and XII in SMA N 2 Bantul Yogyakarta in 2018/2019 Academic Year, totaling 111 students. Intake by using quota random sampling technique by taking 25% of the number of class XII students that is a number of 35 students. Data collection methods in this study used a validated questionnaire with logical validity. Data analysis techniques using multiple regression analysis.The results showed that there was a positive and significant correlation between digital information services and self-adjustment (independence of character) of students majoring in social studies in obtaining higher education information, by knowing the results of the calculation of rx1y = 0.741 with (P) 0,000 kurang dari 0.01, which means there is a positive and significant correlation between digital information services and self-adjustment (independence of character) of students majoring in social studies in obtaining higher education information. Implications in this study, schools should provide an intensive digital information service in accordance with the needs of students, so students will have comprehensive information about several aspects that exist in themselves as well as directions about higher education information services that are expected by students in develop their talents, interests, and potentials, so that they will influence and enhance the attitude of independence of good students.